The Effect of Rewards and Organizational Culture on Job Satisfaction of Private Kindergarten Teachers in Tembilahan District - Annisa Artanti; Rita Kurnia; Dedi Futra (Jurnal PAJAR (Pendidikan dan Pengajaran), 2025)
This study aims to describe the influence The Influence of Rewards and Organizational Culture on Job Satisfaction of Private Kindergarten Teachers in Tembilahan District. The type of research used in this study is correlational research with a quantitative approach. This research was conducted in Tembilahan District. The research subjects were 80 private kindergarten teachers. To analyze the research data, simple linear regression and multiple linear regression were used. Based on the results of the study, it is known that there is a significant influence of the reward function on the job satisfaction of kindergarten teachers in Tembilahan District. This can be seen from the value of Fcount>Ftable (71.717>3.96) with significance (0.000<0.05). With the determination of the reward function on the job satisfaction of kindergarten teachers in Tembilahan District resulting from the study, which is 47.90% and the remaining 52.10% is influenced by other variables that were not studied. There is a significant influence of organizational culture on the job satisfaction of kindergarten teachers in Tembilahan District. This can be seen from the value of Fcount>Ftable (90.774>3.96) with significance (0.000<0.05). With the determination of organizational culture on the job satisfaction of kindergarten teachers in Tembilahan District resulting from the study, which is 53.80% and the remaining 46.20% is influenced by other variables that were not studied. There is a significant influence of rewards and organizational culture on the job satisfaction of kindergarten teachers in Tembilahan District. This can be seen from the value of Fcount>Ftable (48.675>3.12) with significance (0.000<0.05). With the determination of the reward function and organizational culture on the job satisfaction of kindergarten teachers in Tembilahan District, the results of the study were 55.80% and the remaining 44.20% were influenced by other variables that were not studied.